Dialog Antara Maryam Dan Malaikat Jibril Dalam Surah Maryam (Analisis Makna Kontekstual) - Amaliyah, Rara Anidar; Hamsa, Hamsa; Muhammad, Aksa (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
This thesis discusses the dialogue between Maryam and Jibril in Surah Maryam. The essence of this discussion is about dialogue and contextual meaning analysis, with the problem formulation as follows: forms of dialogue and forms of contextual meaning in the dialogue between Maryam and Jibril in Surah Maryam. This research is descriptive qualitative research. This means that this research examines and describes the dialogue between Maryam and Jibril in Surah Maryam by analyzing its contextual meaning. The research approach used is a linguistic-semantic approach by analyzing each problem to be studied. The data collection technique carried out by researchers is through documentation by searching library research data to obtain scientific information. Then the data collected through literature review is data related to the researcher's title as a reference for problems that are deemed appropriate. Researchers also use qualitative methods in analyzing data. The results of this research show that the researcher found 2 verses which were prologue (introductory) dialogues, 7 verses which were dialogues whose dialogue form included direct dialogue between Maryam and Jibril, and 1 verse which was a monologue dialogue between Maryam and herself whose dialogue form included indirect dialogue. Researchers also found 8 verses whose contextual meaning is in the form of context of situations and also emotional context related to the speaker's attitude and conversation situation.